Center-Pivot-Irrigated Corn Silage Cost-Return Budget in Western Kansas - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Haag, Lucas; Holman, John (My University, 2014)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated corn silage production in western Kansas.
MF589_2014_02
Keywords: MF589; Economics; Crops; MF